TRAPEZOİDAL LİNGUİSTİC CUBİC HESİTANT FUZZY TOPSIS METHOD AND APPLİCATİON TO GROUP DECİSİON MAKİNG PROGRAM - A. Fahmi; S. Abdullah; F. Amin (Journal of New Theory)
– In this paper, we define a new idea of trapezoidal linguistic cubic hesitant fuzzy number. We discuss some basic operational laws of trapezoidal linguistic cubic hesitant fuzzy number and hamming distance of trapezoidal linguistic cubic hesitant fuzzy number. Furthermore, we develop Trapezoidal linguistic cubic hesitant fuzzy TOPSIS method to solve the MCDM method based on trapezoidal linguistic cubic hesitant fuzzy TOPSIS method. Finally, an illustrative example is given to verify and demonstrate the practicality and effectiveness of the proposed method